2023
DOI: 10.1002/ptr.7764
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of curcumin plus piperine co‐supplementation in moderate‐to‐high hepatic steatosis: A double‐blind, randomized, placebo‐controlled clinical trial

Abstract: Non-alcoholic Fatty Liver Disease (NAFLD) is a global health problem that can progress to steatohepatitis and cirrhosis. The aim of this study was to determine the effect of curcumin + piperine on cardiometabolic risk factors, as well as hepatic steatosis and fibrosis in NAFLD patients with moderate-to-high hepatic steatosis.Patients diagnosed with moderate-to-high NAFLD by liver sonography were randomized to either curcumin + piperine (500 mg/day curcumin plus 5 mg/day piperine) for 12 weeks (n = 30) or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Among them, liver protection is the most famous treatment effect. Sharifi et al [ 13 ] reported a double-blind, placebo-control, single-center trial. The results showed that non-alcoholic fatty liver disease (NAFLD) patients with moderate-to-high hepatic steatosis oral CUR had significantly reduced blood concentrations of triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), aspartate aminotransferase (AST), and alanine aminotransferase (ALT).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, liver protection is the most famous treatment effect. Sharifi et al [ 13 ] reported a double-blind, placebo-control, single-center trial. The results showed that non-alcoholic fatty liver disease (NAFLD) patients with moderate-to-high hepatic steatosis oral CUR had significantly reduced blood concentrations of triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), aspartate aminotransferase (AST), and alanine aminotransferase (ALT).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anti‐diabetic and anti‐lipidemic effects of this polyphenol have previously been confirmed (Ganji et al, 2021; Mahdavi et al, 2020; Mahdavi, Bagherniya, et al, 2021; Mahdavi, Moradi, et al, 2021; Parsamanesh et al, 2018; Rafiee et al, 2021; Talebi et al, 2020). This phytochemical also has healing effects in many liver‐related diseases, including non‐alcoholic fatty liver disease (NAFLD), hepatic steatosis, and liver fibrosis (Bagherniya et al, 2018; Dadkhah Tehrani et al, 2023; Farzaei et al, 2018; Feng et al, 2019; Hassanizadeh et al, 2023; Heidari et al, 2023; Jalali et al, 2020; Lee et al, 2019; Sharifi et al, 2023; Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%